Plyometric training on sand versus grass: Effects on sprinting, jumping, agility and balance in soccer players - Bonavolontà, V.; Carvutto, R.; Di Gioia, A.; De Candia, M. (Journal of Human Sport & Exercise, 2021)
Soccer is an intermittent high-intensity activity requiring explosive strength and power production by the neuromuscular system. Plyometric training is recognized as an effective method for improving both sprinting and jumping ability through the stretch-shortening cycle. The aim of this study was to compare the effects of plyometric training on sand versus a grass surface on sprinting, jumping, agility, balance ability in soccer players. Sixteen adult soccer players volunteered in the study and were randomly assigned to a plyometric training group performed on sand (PS, n = 8) or on grass (PG, n = 8). Both groups performed 7 weeks of plyometric training on two separate weekly sessions lasting about 1.5 hour. Five-, 10- and 20-meters sprint test, Sargent test and standing long jump test, Illynois Agility test and Stork test were administered to assess sprinting, jumping, agility and balance ability, respectively. After 7 weeks of intervention results showed significative improvements in PS group for sprinting (p < .05), for standing long jump test (p < .05) and for balance (p < .05). Small but not significant differences were found for the other variables. A 7-week plyometric training performed on sand showed improvements on sprinting, jumping and balance respect to the same training performed on grass surface in adult soccer players.